Uzbekistan : Building Blocks for Integrated Transport and Logistics Development - World Bank (World Bank, Washington, DC, 2020)
This document has been produced by the World Bank to underpin the Republic of Uzbekistan’s ‘Strategy for the Development of the Transport System until 2035’ as it continues structural reforms and transitions the country to a competitive market-oriented economy. The policy paper aims to provide a vision to policy makers and practitioners for improving transport and logistics connectivity and service delivery and to define the building blocks of a comprehensive strategy by (a) laying out the higher-level objectives and priority directions for developing the sector, (b) defining the key aspects of advancing the institutional reforms, (c) identifying main transport and logistics gaps and barriers, and (d) presenting opportunities for introducing innovative financing mechanisms and PPPs in transport and logistics. At the same time, the paper points out areas needing further diagnostics and data gathering to better determine deficiencies, calculate transport and logistics costs, and identify further areas for improvement.